Hopper and firing device for secondary battery positive electrode active material using same
The hopper design with a 30° or less opening angle and a crushing mechanism addresses the issue of mixing ratio variations in nickel composite oxide and lithium compounds, resulting in consistent battery performance and improved manufacturing efficiency.
Patent Information
- Application Number
- JP2019062430
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2019-03-28
- Publication Date
- 2025-04-10
- Estimated Expiration
- 2039-03-28
AI Technical Summary
Existing hopper designs for mixing nickel composite oxide and lithium compounds lead to variations in the mixing ratio due to particle size separation and specific gravity separation, resulting in inconsistent battery performance.
A hopper with a cone portion having an opening angle of 30° or less and a discharge portion with a crushing mechanism, which maintains a consistent mixing ratio by minimizing solidified layer formation and ensuring uniform flow.
The hopper design significantly reduces variations in the mixing ratio, leading to consistent battery performance and improved manufacturing efficiency for positive electrode active materials in secondary batteries.
Smart Images

Figure 0007659964000003 
Figure 0007659964000004 
Figure 0007659964000005
Abstract
Description
[Technical field]
[0001] The present invention relates to a hopper and a firing device for firing a positive electrode active material for a secondary battery using the hopper. [Background technology]
[0002] In recent years, with the widespread use of mobile devices such as mobile phones and laptop computers, there is a strong demand for the development of small, lightweight secondary batteries with high energy density. In addition, in the field of eco-friendly vehicles known as xEVs, there is a shift from hybrid electric vehicles (HEVs) to plug-in hybrid electric vehicles (PHEVs) and battery electric vehicles (BEVs), which require high-capacity secondary batteries. BEVs have a shorter driving distance on a single charge than gasoline-powered vehicles, and there is a demand for high-capacity secondary batteries to improve this. A lithium-ion secondary battery is one example of a secondary battery that satisfies such requirements. This lithium-ion secondary battery is composed of a negative electrode, a positive electrode, an electrolyte, etc., and the active materials for the negative electrode and the positive electrode are materials that can extract and insert lithium.
[0003] Lithium-ion secondary batteries are currently the subject of vigorous research and development. In particular, lithium-ion secondary batteries that use layered or spinel-type lithium metal composite oxides as the positive electrode material are capable of achieving a high voltage of around 4 V, and are therefore being put into practical use as batteries with high energy density. The main materials that have been proposed so far are lithium cobalt composite oxide (LiCoO2), which is relatively easy to synthesize, lithium nickel composite oxide (LiNiO2), and lithium nickel cobalt manganese composite oxide (LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2) and lithium manganese composite oxide (LiMn2O4) that uses manganese. Among these, lithium nickel composite oxide (LiNiO₂) has a high capacity and high output, and is attracting attention as a cathode active material for secondary batteries of future environmentally friendly vehicles that satisfies the characteristics required for such, and its demand is rapidly expanding.
[0004] Patent Document 1 discloses a cathode active material for a non-aqueous electrolyte secondary battery composed of a lithium nickel composite oxide represented by the general formula: Li b Ni 1-x-y Co x M y O₂ (wherein M is at least one element selected from Mg, Al, Ca, Ti, V, Cr, Mn, Nb, Zr, and Mo; b is a numerical value satisfying 0.95 ≤ b ≤ 1.03, x is 0 < x ≤ 0.15, y is 0 < y ≤ 0.07, and x + y ≤ 0.16). Further, Patent Document 2 discloses a cathode active material for a non-aqueous electrolyte secondary battery composed of particles of a lithium nickel composite oxide represented by the general formula: Li a Ni 1-x-y Co x Al y O₂ (provided that 0.9 ≤ a ≤ 1.0, 0.10 ≤ x ≤ 0.20, and 0.02 ≤ y ≤ 0.1).
[0005] To obtain the cathode active materials of Patent Documents 1 and 2, it is necessary to bake a mixed powder of nickel composite oxide particles and lithium compound particles. However, since the nickel composite oxide particles and the lithium compound particles have different particle sizes and specific gravities, particle size separation and specific gravity separation are likely to occur. In the mass production process, it is common to store the mixed powder in a large hopper and supply the mixed powder from there to a firing container such as a crucible. Even in this large hopper, particle size separation and specific gravity separation occur, and the mixed ratio of the nickel composite oxide particles and the lithium compound is separated. As a result, it is difficult to supply the mixed powder to a firing container such as a crucible at a constant mixing ratio. And when the mixing ratio of the nickel composite oxide and the lithium compound deviates, for example, as described in Patent Document 1, a large decrease in the battery capacity during charge and discharge cycles, a large amount of gas generation during charging, and gelation of the slurry during electrode production occur.
[0006] To prevent this, in Patent Document 1, a nickel composite hydroxide is oxidatively roasted to form a nickel composite oxide, which is then mixed with a lithium compound. Although gravity separation is less likely to occur in this case than in a mixture of a nickel composite hydroxide and a lithium compound, as described above, the nickel composite oxide and the lithium compound also have large differences in specific gravity and particle size, so gravity separation and particle size separation occur, resulting in a distribution of the mixing ratio in the hopper.
[0007] Patent Document 2 also describes that the variation in the mixing ratio can be suppressed by mixing the precursors thoroughly without destroying their shells. When the materials are mixed and fed to the firing vessel immediately without flowing, as in experimental research or small-scale production, the variation is small. However, when a large hopper is used as in mass production equipment, gravity separation and particle size separation occur due to flow in the hopper, resulting in a distribution in the mixing ratio of the nickel composite oxide and the lithium compound. As a result, the mixed powder with a different mixing ratio is fired depending on the firing vessel, resulting in the formation of a positive electrode active material that causes the above-mentioned decrease in battery capacity and gelation of the slurry.
[0008] The present inventors have found that when any powder raw material, including the raw material for a positive electrode active material for a secondary battery represented by the above-mentioned nickel composite oxide and lithium compound, is supplied using a hopper, one of the causes of variation in the mixing ratio between the powder raw materials is a solidified layer formed in the cone portion of the hopper. Conventional techniques for preventing the formation of a solidified layer in the cone portion of a conventional hopper include Patent Documents 3 to 5. Patent Document 3 discloses an apparatus in which a cone-shaped soft container made of a soft material is placed inside a cone-shaped rigid container to form an airtight gap between the rigid container and the soft container, and an air vent pipe is connected to the rigid container to supply compressed fluid from the air vent pipe to the airtight gap to freely expand the soft container inward and break up blocked granules. Moreover, Patent Document 4 discloses a device including a plate provided on the inner surface in the vicinity of the discharge port and vibration means for vibrating the plate. However, the methods of Patent Documents 3 and 4 destroy the solidified layer that has formed, and therefore although they can improve the variation in the mixing ratio to some extent, they cannot completely prevent the formation of the solidified layer, and therefore cannot provide sufficient improvement.
[0009] Patent Document 5 discloses a method in which an insert cone is provided near the top of the bottom opening of a storage tank and a vane is provided on the insert cone. This method prevents the formation of a solidified layer and improves the variation in the mixing ratio of the mixed powder, but the insert cone suppresses the flow of the powder, slowing down the discharge speed of the powder. In addition, since the insert cone is suspended by a wire, there is a possibility that powder generated by abrasion of the wire or the suspension ring, or powder generated by the contact of the insert cone with the hopper wall, may be mixed in due to shaking. [Prior art documents] [Patent documents]
[0010] [Patent Document 1] JP 2015-216105 A [Patent Document 2] JP 2017-188211 A [Patent Document 3] JP 2001-039489 A [Patent Document 4] JP 2008-222272 A [Patent Document 5] Japanese Patent Application Publication No. 6-080189 Summary of the Invention [Problem to be solved by the invention]
[0011] SUMMARY OF THE PRESENT EMBODIMENT In view of the above problems, an object of the present invention is to provide a hopper capable of reducing the variation in the mixing ratio of all kinds of mixed powder raw materials. Another object of the present invention is to provide an apparatus for sintering a positive electrode active material for a secondary battery, which is capable of producing the positive electrode active material for a secondary battery with reduced variation in the mixing ratio between the raw materials. [Means for solving the problem]
[0012] The hopper of the first invention is a hopper for supplying a mixed powder raw material containing a nickel composite oxide and a lithium compound, which have different physical properties, and includes a cylindrical hopper portion, a cone-shaped cone portion connected to the lower end of the hopper portion, and a discharge portion connected to the lower end of the cone portion, and the opening angle a of the cone portion is: 40° or less Yes R It is characterized by: The second invention In the first aspect of the present invention, the hopper is characterized in that the opening angle a of the cone portion is 30° or less. The third invention In the hopper of the first invention, the maximum angle of repose of the mixed powder raw material is 63° or more and 65° or less. No. 4 The sintering device for a positive electrode active material for a secondary battery of the invention includes a plurality of setters filled with objects to be sintered, a supply section that supplies the objects to be sintered to each of the setters, a sintering furnace that sinters the objects supplied to each of the setters, a transport section that transports each of the setters from the supply section to the sintering furnace and transports each of the setters carrying the objects sintered in the sintering furnace out of the sintering furnace, and a discharge section that discharges the objects from each of the setters, and is characterized in that the hopper described in claim 1 is used as a device for supplying the mixed powder raw material in the supply section. No. 5 The apparatus for baking a positive electrode active material for a secondary battery according to the present invention is 4 In the present invention, the discharge section is characterized by having a crushing mechanism for crushing the fired products discharged from each of the setters. No. 6 The apparatus for baking a positive electrode active material for a secondary battery according to the present invention is 5 In the present invention, the crushing mechanism is a roll crusher, and is characterized by being equipped with a cooling mechanism for cooling the rolls that come into contact with the high-temperature fired material. No. 7 The apparatus for baking a positive electrode active material for a secondary battery according to the present invention is 4 In the present invention, at least one of the supply unit, the sintering furnace, the discharge unit, and the crushing mechanism has a function of maintaining the oxygen concentration around the working space at 80% or more. No. 8 The firing apparatus for a positive electrode active material for a secondary battery of the present invention comprises: 4th~7th In any of the inventions, the fired product contains lithium (Li), nickel (Ni), cobalt (Co), and other elements (M), and the atomic ratio of each element is Li:Ni:Co:M = s:(1 - x - y):x:y (where 0.93 < s < 1.03, 0.00 ≦ x ≦ 0.35, 0.03 ≦ y ≦ 0.35, and M is one or more transition metals, alkaline earth metals, base metals, or metalloids), and is characterized by being a lithium nickel composite metal oxide.
Advantages of the Invention
[0013] According to the first invention, by setting the opening angle a of the cone part to 40° or less a mixed powder raw material containing a nickel composite oxide and a lithium compound having different physical properties such as specific gravity and particle size When , On the inner wall of the cone a part of the mixed powder raw material Even if a solidified layer occurs to which the mixed powder raw material of mixing ratio Reduce the variation in can be discharged while maintaining it. Therefore, all the positive electrode materials for secondary batteries obtained by firing the mixture discharged from the hopper can contribute to exhibiting equivalent battery performance. According to the second invention, By setting the cone opening angle a to 30° or less, when the mixed powder raw material contains a nickel composite oxide and a lithium compound with different physical properties such as specific gravity and particle size, a solidified layer in which part of the mixed powder raw material adheres to the inner wall of the cone is not formed, and the mixed powder raw material can be discharged while keeping the variation in the mixing ratio of the mixed powder raw material very small. Therefore, all positive electrode materials for secondary batteries obtained by firing the mixture discharged from the hopper can contribute to exhibiting the same battery performance. According to the third invention, When the maximum angle of repose of the mixed powder raw material is 63° or more and 65° or less, the cone opening angle a is 40° or less or 30° or less, so even if a solidified layer is formed in which part of the mixed powder raw material adheres to the inner wall of the cone, the mixed powder raw material can be discharged while keeping the variation in the mixing ratio of the mixed powder raw material small. Therefore, all the positive electrode materials for secondary batteries obtained by firing the mixture discharged from the hopper can contribute to exhibiting the same battery performance. The 4 invention, since the setter in the supply part is supplied with the mixed powder raw material with a smaller variation in the mixing ratio than the hopper of the first invention, the mixing ratio of the mixed powder raw material of the fired positive electrode active material also remains with a smaller variation, and it becomes possible to easily manufacture a high-capacity positive electrode active material for secondary batteries. The 5 invention, since the fired product solidified by firing can be pulverized, it can be made into an appropriate particle size for use as a positive electrode active material for secondary batteries. Further, since the pulverized fired product can be subjected to a water washing process, the fired product can be washed more uniformly. The 6According to the invention, the sintered material can be pulverized simply by supplying it between a pair of rolls, and since the rolls are cooled by a cooling mechanism, they do not become excessively hot and the physical properties of the sintered material that comes into contact with the rolls are not changed. No. 7 According to the invention, an atmosphere suitable for sintering is maintained from the supply section through the sintering furnace to the discharge section, allowing the mixed powder raw material to react sufficiently, and changes in the physical properties of the sintered product after sintering can be suppressed, resulting in a sintered product with the desired physical properties. No. 8 According to the present invention, it is possible to obtain a fired lithium-nickel composite metal oxide having appropriate physical properties, which is a raw material for a positive electrode active material for a lithium ion secondary battery. [Brief description of the drawings]
[0014] [Figure 1] FIG. 2 is an explanatory diagram of a hopper 50 according to one embodiment of the present invention. [Diagram 2] 1 is a schematic plan view of a baking device 1 according to one embodiment of the present invention. [Diagram 3] 3 is a schematic cross-sectional view taken along line III-III in FIG. 2. [Figure 4] FIG. 1(a) is a schematic diagram of a mixed powder discharge state of a hopper 50 of the present invention, and FIG. 1(b) is a schematic diagram of a mixed powder discharge state of a hopper 100 of a comparative example. [Diagram 5] FIG. 1 is a diagram showing an example of a method for producing a positive electrode active material for a lithium ion secondary battery. [Figure 6] FIG. 1 is a diagram showing an example of a method for producing a nickel composite oxide. [Figure 7] FIG. 2 is a diagram showing an example of a treatment process for a lithium nickel composite oxide after calcination. [Figure 8] FIG. 2 is a diagram showing an evaluation secondary battery used in the examples. [Figure 9] FIG. 2 is an explanatory diagram of the angle of repose. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0015] Hereinafter, the embodiments of the present invention will be described in the following order of (1) to (6) with reference to the drawings. However, the present invention is not limited to the embodiments described below. In the drawings, the embodiments may be expressed diagrammatically or at a different scale as appropriate. (1) Hopper (2) A baking device using the above hopper (3) Manufacturing method of positive electrode active material for lithium-ion secondary battery (4) Positive electrode active material for lithium-ion secondary batteries (5) Lithium-ion secondary battery (6) Example of lithium-ion secondary battery
[0016] (1) Hopper The hopper 50 according to one embodiment of the present invention is a hopper that supplies a mixed powder raw material in which a plurality of types of powder are mixed. In this specification, "multiple kinds of powders" refers to two or more kinds of powders having different physical properties such as specific gravity, particle size, composition, etc., and a mixture of these powders is called a mixed powder raw material. An example of such a mixed powder raw material is a calcined raw material for a positive electrode active material for a secondary battery, such as a lithium compound and a nickel-cobalt composite oxide. Since such multiple types of powder have different specific gravities and particle sizes, even if they are mixed at a constant ratio, the mixing ratio may change partially when flowing through the hopper. If the mixing ratio changes, the properties of the mixed powder will change, so the hopper of the present invention is suitable for supplying powder raw materials whose mixing ratio needs to be kept constant to avoid this. The multiple types of powder are not limited to two types, but may include three or more types. The present invention can also be applied to supplying multiple types of powder with the same specific gravity.
[0017] 1 is composed of a cylindrical hopper section 51, a cone-shaped cone section 52 connected to the lower end of the hopper section 51, and a discharge section 53 connected to the lower end of the cone section 52. A valve 54 is provided in the discharge section 53 to control the discharge of the mixed powder raw material from the hopper. The opening angle a of the cone portion 52 is set to an angle expressed by the formula (1) when the maximum value of the angle of repose of the mixed powder raw material is b. a≦180-2b-10...Equation (1) The opening angle a is the angle at which the opposing inner walls of a cone intersect with each other.
[0018] 1, the crossing angle of the inner wall 52a of the cone portion 52 with respect to the horizontal plane is the maximum repose angle b+α of the mixed powder raw material, where α is 5° in the illustrated embodiment. In this case, the angle between the diagonal inner walls 52, that is, the opening angle a, is (180-2b-10). The opening angle a is the maximum angle in the above case, and smaller angles are also included. In other words, the present invention also includes an opening angle a in which the cone portion 52 has a sharper taper. The angle of repose is the angle between the slope of the powder peak that forms and the horizontal plane when the powder pw is dropped from a certain height and remains stable without collapsing spontaneously, as shown in Figure 9. This angle of repose c is determined by the size, shape, surface condition, weight, etc. of the particles, and the angle of repose c of powders that flow easily is small, while the angle of repose c of powders that do not flow easily is large. In addition, this angle of repose has a range depending on the properties of the powder, but in the present invention, the maximum value b is used.
[0019] In the hopper 50 of the present invention, the inner wall 52a of the cone portion 52 is inclined at an angle larger than the maximum value b of the angle of repose of the mixed powdered raw material handled in the hopper. As a result, the mixed powder raw material pw charged into the hopper 50 flows downward at an angle exceeding the maximum repose angle b on the inner wall 52a of the cone section 52, so that no solidified layer is formed due to the mixed powder raw material pw stagnating.
[0020] In the hopper 100 of the comparative example shown in Fig. 4(b), the opening angle a of the cone part 102 is larger than (180-2b-10), so the flow of the mixed powder raw material pw becomes poor and a solidified layer sl is formed. As a result, there are parts with high fluidity and parts with low fluidity, and the variation in the mixing ratio of the mixed powder raw material pw becomes large. In contrast, in the hopper 50 of the present invention shown in Fig. 4(a), the opening angle a of the cone portion 52 is (180-2b-10) or less, so the entire amount of the mixed powder raw material pw slides down on the inner wall 52a of the cone portion 52. As a result, a solidified layer sl of the mixed powder raw material pw is not formed on the inner wall surface of the cone portion 52, and part of the mixed powder raw material pw (raw material in the area close to the inner wall surface) does not stagnate and flows smoothly, so that the mixing ratio of the mixed powder raw material pw is less likely to change. Therefore, it is possible to suppress the variation in the mixing ratio to a small value.
[0021] Furthermore, the fact that there is little variation in the mixing ratio when the material is discharged from the hopper 50 means that the mixing ratio when it was put into the hopper 50 is almost maintained, which means that the physical properties of the mixed powder raw material can be maintained as desired and the mixed powder raw material can be supplied to the next process. For example, when the mixed powder raw material is a raw material for a positive electrode material for a secondary battery, the material to be sintered supplied by the hopper 50 is sintered in a sintering device, and the obtained sintered powder can all contribute to achieving the same battery performance.
[0022] (2) Baking equipment A baking device 1 according to one embodiment of the present invention will be described with reference to Figs. This baking apparatus 1 is a baking apparatus that uses a hopper 50 in FIG. 1 as a component of the supply section 10 to supply the material to be baked (the mixed powder raw material is referred to as the material to be baked at the stage of being baked in the baking apparatus). 2 and 3, the baking device 1 includes a baking furnace 2 that bakes the object to be baked into a baked product, a plurality of setters S on which the object to be baked is placed, a supply section 10 that supplies the object to be baked to the setters S, a discharge section 20 that discharges the object baked in the baking furnace 2 from the setters S (the object to be baked after baking is completed is called the baked product), and a conveying section 5 that conveys the setters S. The plurality of setters S are moved by the conveying section 5 in the order of the supply section 10, the baking furnace 2, and the discharge section 20, so that the objects to be baked can be baked continuously. Each part of the baking device 1 will be described in detail below.
[0023] (Supply section 10) 2 and 3, the supply unit 10 is provided so as to be located above a path along which the setter S moves in the supply and conveyance unit 5a described below. The supply unit 10 includes a hopper 50 that supplies mixed powder raw materials. Mixed powder raw materials mixed at a predetermined mixing ratio are supplied to the hopper 50 from a flexible container 80 or the like. A known filling machine 15 may be placed between the hopper 50 and the setter S located above the conveying and supplying section 5a. The filling machine 15 is provided when it is necessary to improve the filling property of the mixed powder raw material into the setter 5, but it does not have to be provided when this is not necessary. When the filling machine 15 is not provided, the hopper 50 should be placed at a lower position than the vertical position shown in the figure.
[0024] In this supply section 10, when the setter S moves below the hopper 50, the valve 54 is opened and closed to discharge a predetermined amount of mixed powder raw material, so that the mixed powder raw material can be supplied into the setter S as the material to be fired. It is desirable that the opening and closing of the valve 54 of the hopper 50 is controlled so as to be linked to the operation of the supply and conveyance unit 5a. For example, when the setter S is placed below the hopper 50, the supply and conveyance unit 5a temporarily stops conveying the setter S, and upon receiving the stop signal, the valve 54 of the hopper 50 opens and the material to be baked is supplied to the setter S. Then, when a predetermined amount of the material to be baked is supplied to the supplier 12, the valve 54 of the hopper 50 closes, but the supply and conveyance unit 5a can be made to move upon receiving a signal that the valve is closed. Alternatively, the supply and transport section 5a may supply the material to be fired from the supply section 10 to the setter S while moving the setter S, without temporarily stopping the transport of the setter S.
[0025] (Setter S) 2 and 3, the symbol S indicates a setter. This setter S is formed in a box shape with an opening Sa at the top and a hollow space Sh inside, and is also called a sagger. With the object to be fired housed in the space Sh of this setter S, the object to be fired is fired into a fired object in a firing furnace 2 described later.
[0026] The setter S is formed of a material that can maintain its shape even at the temperature at which the object to be sintered is sintered and does not react with the substances in the object to be sintered. For example, when a lithium composite metal oxide is sintered, the setter S is formed of a material that has corrosion resistance against lithium even at 600 to 900°C, which is the sintering temperature range of the lithium composite metal oxide. Specifically, alumina (Al2O3), mullite (3Al2O3·2SiO2), cordierite (2MgO·2Al2O3·5SiO2), silicon nitride (Si3N4), sialon (Si3N4·Al2O3), magnesia (MgO), zirconia (ZrO2), or beryllia (BeO) can be used as the material for the setter S. In particular, high-purity alumina or alumina containing ZrO2 is preferable because it has excellent corrosion resistance against lithium. In addition, mullite and cordierite are inexpensive and have relatively good corrosion resistance, and because of their overall low cost, they are suitable as materials for setter S when mass-producing fired products.
[0027] The setter S does not have to be entirely made of the above-mentioned materials. At least the surface of the setter S that comes into contact with the object to be sintered (i.e., the inner surface of the setter S) needs to be made of a material that does not react with the substances in the object to be sintered. For example, when sintering a lithium composite metal oxide, the inner surface of the setter S made of a metal or the like may be covered with alumina, mullite, or the like. Even in this case, the material that forms the main body of the setter S needs to be a material that can maintain its shape at the temperature at which the object to be sintered is sintered into the sintered product.
[0028] (Transportation section 5) 2 and 3, the firing apparatus 1 is equipped with a conveying section 5 that conveys the plurality of setters S. The conveying section 5 is composed of a supply conveying section 5a, a firing furnace conveying section 5b, a discharge conveying section 5c, and a return conveying section 5d.
[0029] The supply and transport section 5a successively carries into the firing furnace 2 a plurality of setters S to which the objects to be fired have been supplied in the supply section 10. The firing furnace transport section 5b moves a plurality of setters S within the firing furnace 2. The discharge / transport section 5c continuously carries out a plurality of setters S, in which the fired products are accommodated, from the firing furnace 2 and supplies them to the discharge section 20. The return conveying section 5d conveys the plurality of setters S from which the fired products have been discharged in the discharging section 20 to the supplying section 10. Note that equipment for cleaning the setters S (e.g., a suction device, etc.) may be provided midway in the return conveying section 5d.
[0030] The conveying section 5 may be configured such that the supply conveying section 5a, the firing furnace conveying section 5b, the discharge conveying section 5c, and the return conveying section 5d (hereinafter sometimes simply referred to as each conveying section 5a to 5d) move the multiple setters S at the same speed, or the multiple setters S may be moved at different speeds. Of course, the multiple setters S may be moved at different speeds within each of the conveying sections 5a to 5d.
[0031] As described above, each of the transport sections 5a to 5d may transport a plurality of setters S, and the transport mechanism is not particularly limited. For example, a belt conveyor, a chain conveyor, a roller conveyor, etc. may be used as the transport mechanism. The transport sections 5a to 5d may all have the same transport mechanism, or may use different transport mechanisms. 2 and 3 show an example in which each of the transport sections 5a to 5d is formed by a roller conveyor.
[0032] Although the materials of the components constituting each of the transport sections 5a to 5d are not particularly limited, it is preferable to use materials such as alumina and mullite that are resistant to corrosion by lithium. If such materials are used for the surfaces of the components, damage caused by lithium hydroxide or the like can be prevented in the event that lithium hydroxide or the like scatters from the sintered object.
[0033] (Firing furnace 2) In Fig. 2 and Fig. 3, the reference numeral 2 denotes a firing furnace of the firing device 1 of this embodiment. This firing furnace 2 is a continuous firing furnace that fires the object to be fired into a fired product while moving it. The firing furnace 2 is provided with the above-mentioned firing furnace conveying section 5b, and is capable of firing the object to be fired into a fired product while moving a plurality of setters S containing the object to be fired. For example, a known continuous firing furnace such as a roller hearth kiln, a pusher furnace, or a conveyor furnace can be used as the firing furnace 2 of the firing device 1 of this embodiment. In addition, when the firing furnace 2 itself has a transport mechanism for transporting the setter S, the object to be fired, etc., this transport mechanism may be used as the firing furnace transport section 5b.
[0034] The firing furnace 2 can maintain the temperature of the internal space 2h at a predetermined temperature. There is no particular limitation on the method for maintaining the temperature of the internal space 2h at a predetermined temperature in the firing furnace 2. For example, the temperature of the space 2h in the firing furnace 2 can be maintained at or above the predetermined temperature by an electric heater, a gas heater, a heat medium heater, or the like.
[0035] When the firing furnace 2 has a uniform heating zone 2a, a temperature increasing zone 2b, and a temperature decreasing zone 2c, the temperature in each zone is adjusted as follows. Also, the travel time of the fired product in each zone, that is, the speed at which the transport unit 5 transports the setter S, is adjusted as follows. First, the soaking zone 2a is an area where the material to be sintered is sintered into a sintered product. In this soaking zone 2a, the temperature of the space is maintained at a temperature at which the material to be sintered can be sintered into a sintered product. The time for each setter S to move through the soaking zone 2a is adjusted so that the material to be sintered in each setter S can be sintered into a sintered product. As described above, oxygen gas is introduced into the soaking zone 2a to create an atmosphere in which the material to be sintered or the sintered product does not change in physical properties. The temperature rise zone 2b is a region where the temperature of the material to be sintered is raised to a predetermined temperature so that the sintering in the soaking zone 2a is performed appropriately. In the temperature rise zone 2b, the temperature of the space and the movement time of the material to be sintered are adjusted so that the temperature of the material to be sintered rises to a predetermined temperature. Specifically, the temperature of the space and the movement time of the material to be sintered are adjusted in the temperature rise zone 2b so that the material to be sintered gradually approaches the temperature of the soaking zone 2a. In other words, the temperature of the temperature rise zone 2b is adjusted so that the temperature gradually rises from the entrance to the exit so that a sudden temperature rise does not cause abnormal reactions of the substances in the material to be sintered. As described above, oxygen gas is also introduced into the temperature rise zone 2b so that the atmosphere does not change the physical properties of the material to be sintered. The temperature-reducing zone 2c is an area where the temperature of the material to be sintered is reduced to a predetermined temperature, in contrast to the temperature-raising zone 2b. If the material sintered in the soaking zone 2a is exposed to room temperature air as it is, the temperature of the material may change suddenly, causing problems such as deterioration of the material and changes in physical properties such as specific surface area due to contact with air at high temperatures. Therefore, in the temperature-reducing zone 2c, the temperature of the space and the movement time of the material are adjusted so that the temperature of the material gradually decreases, so that the temperature of the material does not deteriorate even if it comes into contact with room temperature air at the stage when it is discharged from the firing furnace 2, and the atmosphere of the temperature-reducing zone 2c is made equivalent to that of the soaking zone 2a.
[0036] For example, lithium hydroxide (LiOH) and nickel composite hydroxide (Ni 0.91 Co 0.04 Al 0.05 (OH)2) mixture to form lithium complex metal oxide (LiNi 0.91 Co 0.04 Al 0.05Consider the case of calcining a mixture of lithium composite metal oxide and fluorine-containing ...
[0037] (Discharge section 20) 2 and 3, the discharge section 20 is disposed between the discharge conveying section 5c and the return conveying section 5d. The discharge section 20 includes a crushing mechanism 21 that crushes the baked object (the object to be baked after baking) in the setter S into small lumps or powder, and a baked object supplier (not shown) that supplies the baked object in the setter S to the crushing mechanism 21.
[0038] The baked product supplying device inverts the setter S transported on the discharge conveying section 5c and supplies the baked product in the setter S to the crushing mechanism 21. This baked product supplying device is not particularly limited as long as it can invert the setter S. For example, a device equipped with an arm that holds the setter S and inverts it can be used. Note that it is desirable for the baked product supplying device to have a function of transferring the setter S from the discharge conveying section 5c to the return conveying section 5d after inverting the setter S.
[0039] The crushing mechanism 21 is not particularly limited as long as it has a function of crushing the baked material supplied from the baked material supply device. For example, as shown in Figures 2 and 3, if it has a pair of rolls 22, 22 arranged at a predetermined interval, the baked material can be sandwiched between the pair of rolls 22, 22 and crushed. In other words, if a roll crusher is used as the crushing mechanism 21, the baked material can be crushed by supplying it between the pair of rolls.
[0040] It is preferable to provide a cooling mechanism for supplying and discharging cooling water to the inside of the rolls 22, 22 of the roll crusher. If the rolls 22 can be cooled by the cooling mechanism, the roll surface does not become excessively hot, and the physical properties of the fired material that comes into contact with the rolls are not changed.
[0041] In addition to the roll crusher, a jaw crusher or the like can be used. In addition, when crushing to a particle size of a few millimeters or less, a pin mill, a hammer mill, a jet mill, or the like can be used in combination with the roll crusher or jaw crusher. Furthermore, the crushing mechanism 21 may have a function of transporting the lumps or powder formed by crushing the fired material to the next process, or may be configured to discharge the lumps or powder onto a conveyor or the like that transports them to the next process.
[0042] The pulverizing mechanism 21 can pulverize the sintered product that has hardened due to sintering, so that it can be made into a particle size suitable for use in a positive electrode active material for a secondary battery. In addition, the pulverized sintered product can be subjected to a water washing step, so that the sintered product can be washed more uniformly.
[0043] (Firing atmosphere maintenance mechanism) The baking apparatus 1 of the present invention is preferably provided with a mechanism for maintaining the oxygen concentration in the working space of each portion at 80% or more. 1) It is desirable that the supply unit 10 has a function of maintaining a predetermined atmosphere inside the valve 54 of the hopper 50. For example, if it has a function of introducing oxygen into the valve 54 of the hopper 50, the atmosphere around the material to be sintered inside the valve 54 of the hopper 50 can have an oxygen concentration of 80% or more. In other words, the atmosphere inside the valve 54 of the hopper 50 can be made to be one in which the physical properties of the material to be sintered do not change. The supply unit 10 may also have a hood or the like that covers the setter S (the setter S arranged below the supply device 12) to which the material to be sintered is supplied from the valve 54. In this case, the material to be sintered supplied to the setter S from the valve 54 and the material to be sintered inside the setter S can also be maintained in a predetermined atmosphere.
[0044] 2) The firing furnace 2 has a function of maintaining the space 2h inside, that is, the object to be fired and the surroundings of the object to be fired, in a predetermined atmosphere. The predetermined atmosphere means an atmosphere suitable for firing the object to be fired into a fired object. For example, in the case of firing a lithium composite metal oxide, the predetermined atmosphere corresponds to an oxygen atmosphere in which the space 2h in the firing furnace 2 is maintained at a predetermined oxygen concentration (e.g., 80% or more). There is no limitation on the method of maintaining the space 2h in the firing furnace 2 in the above-mentioned oxygen atmosphere. For example, an oxygen introduction device that introduces oxygen into the space 2h in the firing furnace 2 is provided, and oxygen gas is introduced into the space 2h by this oxygen introduction device. Then, the space 2h in the firing furnace 2 can be maintained in an oxygen atmosphere maintained at a predetermined oxygen concentration (e.g., 80% or more). Oxygen gas is introduced into the heat soaking zone 2a so as to obtain an oxygen concentration necessary for the firing reaction. Oxygen gas is also introduced into the temperature-lowering zone 2c so as to create an atmosphere in which the physical properties of the fired material do not change.
[0045] 3) It is desirable that the interior of the discharge section 20, particularly the crushing mechanism 21, has a function of maintaining a predetermined atmosphere in the space in which the fired material is crushed or the space to which the fired material is supplied. For example, if the crushing mechanism 21 has a function of introducing oxygen into the interior, the atmosphere surrounding the fired material supplied to the crushing mechanism 21 can be made to have an oxygen concentration of 80% or more. In other words, it is possible to prevent the physical properties of the fired material from changing while it is being crushed in the crushing mechanism 21.
[0046] 4) If a hood or the like is provided to cover the area from the supply section 10 to the entrance of the firing furnace 2, a predetermined atmosphere can be maintained around the material to be fired while it is moving from the supply section 10 to the firing furnace 2. This makes it possible to suppress changes in the physical properties of the material to be fired while it is moving from the supply section 10 to the firing furnace 2. Furthermore, if there is a hood or the like that covers the area from the firing furnace 2 to the discharge section 20, the atmosphere around the fired material can be maintained at a predetermined level while the fired material is moving from the firing furnace 2 to the discharge section 20. This makes it possible to prevent the physical properties of the fired material from changing while it is moving from the firing furnace 2 to the discharge section 20.
[0047] The term "work space" in the claims refers to the space in the supply section 10, the firing furnace 2, and the discharge section 20 (including the crushing mechanism 21) through which the material to be fired moves and undergoes the necessary treatment.
[0048] (3) Method for producing positive electrode active material for lithium ion secondary battery The hopper and the sintering device of the present invention can be suitably used for supplying and sintering raw materials for a positive electrode active material for a secondary battery. Positive electrode active material for secondary battery to which the present invention is applied Quality There is no particular restriction, but lithium nickel composite oxide is Things This can be given as one example. The lithium nickel composite oxide contains lithium (Li), nickel (Ni), cobalt (Co), and other elements (M), and the atomic ratio of each element is Li:Ni:Co:M = s:(1 - x - y):x:y (where 0.93 < s < 1.03, 0.00 ≦ x ≦ 0.35, 0.03 ≦ y ≦ 0.35, and M is one or more transition metals, alkaline earth metals, base metals, or metalloids). Further, the above lithium nickel composite oxide (hereinafter, also simply referred to as "composite oxide") has a crystal structure of a layered structure and may include a form of secondary particles formed by aggregation of primary particles.
[0049] FIG. 5 is a diagram showing an example of a method for manufacturing a positive electrode active material for a lithium ion secondary battery. As shown in FIG. 5, the method for manufacturing a positive electrode active material includes The raw material for the positive electrode active material obtaining a lithium mixture containing a nickel composite oxide and a lithium compound (mixing step: step S10), and firing the lithium mixture (firing step: step S30). Hereinafter, each step will be described.
[0050] (Mixing step: step S10) First, a nickel composite oxide and a lithium compound are mixed to obtain a lithium mixture (step S10). By using a nickel composite oxide as a raw material, a highly crystalline lithium nickel composite oxide can be obtained with high productivity by firing for a very short time. Hereinafter, each raw material used in the mixing step (step S10) will be described.
[0051] (Nickel composite oxide) The nickel composite oxide is a composite oxide containing nickel and other transition metals, alkaline earth metals, base metals, or metalloids. In the following description, as an example of the nickel composite oxide, an oxide containing nickel and cobalt (hereinafter, also referred to as "nickel cobalt composite oxide") will be described.
[0052] The nickel-cobalt composite oxide may contain, in addition to nickel and cobalt, another element M. The element M is at least one element selected from transition metals other than nickel and cobalt, alkaline earth metals, base metals, and semimetals, and examples thereof include manganese, molybdenum, tungsten, aluminum, silicon, boron, niobium, vanadium, and titanium.
[0053] The nickel-cobalt composite oxide may contain, for example, nickel (Ni), cobalt (Co), and an element M, and the atomic ratio (molar ratio) of each element may be expressed as Ni:Co:M=(1-xy):x:y (0.00≦x≦0.35, 0.03≦y≦0.35). The ratio of each element contained in the nickel-cobalt composite oxide is inherited to the lithium-nickel composite oxide. Therefore, the composition of the nickel-cobalt composite oxide as a whole can be made the same as the composition of metals other than lithium in the lithium-nickel composite oxide to be obtained.
[0054] The nickel-cobalt composite oxide can be obtained, for example, by oxidizing a nickel-cobalt composite hydroxide used as a precursor of a positive electrode active material. When the nickel-cobalt composite oxide is used, the amount of water vapor generated during the calcination of the lithium mixture is reduced, the reaction is significantly facilitated, and the calcination time can be significantly shortened. Hereinafter, an example of a method for producing the nickel-cobalt composite oxide will be described. The nickel-cobalt composite oxide may be obtained by other methods.
[0055] Fig. 6 is a diagram showing an example of a method for producing a nickel-cobalt composite oxide. For example, the nickel-cobalt composite oxide can be obtained by a method including oxidative roasting (step S2) of a nickel-cobalt composite hydroxide obtained by crystallization (step S1). The nickel-cobalt composite hydroxide obtained by crystallization has a uniform composition throughout the particles, and the composition of the finally obtained positive electrode active material is also uniform. The nickel-cobalt composite oxide may be obtained by a method other than crystallization. Each step for producing the nickel-cobalt composite oxide will be described below.
[0056] (Crystallization process: Step S1) The nickel-cobalt composite hydroxide is obtained by supplying a neutralizing agent or the like to an aqueous solution containing a salt containing nickel (Ni salt), a salt containing cobalt (Co salt), and a salt containing element M, and crystallizing (step S1). As a specific example, the nickel-cobalt composite hydroxide can be produced by neutralizing an aqueous solution containing a nickel salt, a cobalt salt, and a salt of element M with stirring in the presence of a complexing agent such as an ammonium ion donor, and carrying out a crystallization reaction. The nickel-cobalt composite hydroxide obtained by the crystallization method is composed of secondary particles formed by agglomeration of primary particles, and the positive electrode active material obtained by using this nickel-cobalt composite hydroxide particle as a precursor is also composed of secondary particles formed by agglomeration of primary particles. As the metal salt used in preparing the aqueous solution containing the above metal salt, for example, sulfates, nitrates, and chlorides of Ni, Co, and element M can be used.
[0057] The nickel-cobalt composite hydroxide can contain nickel (Ni), cobalt (Co), and optionally other metals (M), and the molar ratio of each element is preferably expressed as Ni:Co:M=1-xy:x:y (0.00≦x≦0.35, 0.03≦y≦0.35). The ratio of each element contained in the nickel-cobalt composite hydroxide is inherited by the nickel-cobalt composite oxide and the lithium-nickel composite oxide. Therefore, the composition of the nickel-cobalt composite hydroxide as a whole can be made similar to the composition of metals other than lithium in the lithium-nickel composite oxide to be obtained.
[0058] The crystallization method is not particularly limited, and for example, a continuous crystallization method, a batch method, etc. can be used. The continuous crystallization method is, for example, a method of continuously recovering nickel-cobalt composite hydroxide overflowing from a reaction vessel, and can easily produce a large amount of nickel-cobalt composite hydroxide having the same composition. In addition, since the nickel-cobalt composite oxide obtained by the continuous crystallization method has a wide particle size distribution, it is possible to improve the packing density of the mixed powder raw material when it is packed into a setter. The particle size of the nickel-cobalt composite hydroxide is, for example, 1 μm or more and 50 μm or less. The batch method can obtain nickel-cobalt composite hydroxide having a more uniform particle size and a narrow particle size distribution. The nickel-cobalt composite hydroxide obtained by the batch method can react more uniformly with a lithium compound during firing. In addition, the nickel-cobalt composite hydroxide obtained by the batch method can reduce the inclusion of fine powder, which is one of the causes of deterioration of cycle characteristics and output characteristics when used in a secondary battery.
[0059] (Oxidation roasting: step S2) Next, the nickel-cobalt composite hydroxide is subjected to oxidizing roasting (heat treatment) to obtain a nickel-cobalt composite oxide (step S2). The conditions of the oxidizing roasting are not particularly limited as long as the nickel-cobalt composite hydroxide is mostly converted to a nickel-cobalt composite oxide, but for example, the temperature of the oxidizing roasting is preferably 600°C or more and 800°C or less. If the temperature of the oxidizing roasting is less than 600°C, moisture may remain in the nickel-cobalt composite hydroxide (precursor) and oxidation may not proceed sufficiently. On the other hand, if the temperature of the oxidizing roasting is more than 800°C, the composite oxides may bond together to form coarse particles. In addition, if the temperature of the oxidizing roasting is too high, a lot of energy is used, so that productivity decreases from the viewpoint of cost, and it is not industrially suitable.
[0060] The time of the oxidizing roasting is preferably, for example, 0.5 hours or more and 3.0 hours or less. If the time of the oxidizing roasting is less than 0.5 hours, the oxidation of the nickel-cobalt composite hydroxide may not proceed sufficiently. On the other hand, if the time of the oxidizing roasting is more than 3.0 hours, the energy cost increases and the productivity decreases, which is not industrially suitable.
[0061] (Lithium compounds) Returning to Fig. 5, the lithium compound to be mixed with the nickel composite oxide (nickel-cobalt composite oxide shown in Fig. 6) will be described. The lithium compound is not particularly limited, and a known lithium compound can be used, for example, lithium hydroxide, lithium nitrate, lithium carbonate, lithium acetate, or a mixture thereof. Among these, lithium hydroxide and lithium carbonate are preferably used.
[0062] The lithium compound is preferably lithium hydroxide from the viewpoints of increasing the reactivity during sintering and shortening the sintering time.
[0063] The lithium hydroxide may be a hydrate such as lithium hydroxide monohydrate (LiOH HO) or an anhydrous such as anhydrous lithium hydroxide (LiOH). Among them, anhydrous lithium hydroxide is preferred, and lithium hydroxide having a moisture content of 1.5% or less and a total carbon content of 1.0% or less is more preferred. Lithium hydroxide with a moisture content of 1.5% or less and a total carbon content of 1.0% or less can be obtained, for example, by heat treating lithium hydroxide hydrate (LiOH·HO). When such lithium hydroxide is used, the generation of moisture in the firing step (step S30) is suppressed, thereby accelerating the synthesis reaction of the lithium nickel composite oxide and shortening the firing time.
[0064] (Lithium mixture) The mixing ratio of the nickel composite oxide and the lithium compound shown in the process diagram of FIG. 5 is such that the ratio (Li / Me ratio) of the total number of atoms (Me) of nickel, cobalt, and aluminum in the nickel composite oxide to the number of lithium atoms (Li) is in the range of more than 0.93 and less than 1.03. If the Li / Me ratio is 0.93 or less, some of the nickel composite oxide may remain unreacted in the firing step (step S30), and sufficient battery performance may not be obtained. On the other hand, if the Li / Me ratio is 1.03 or more, sintering may be promoted in the firing step (step S30), the fired product may become hard and difficult to crush, or the particle size and crystallite size of the lithium nickel composite oxide obtained may become too large, and sufficient battery performance may not be obtained. The role of the hopper (FIG. 1) of the present invention is to keep this mixing ratio (Li / Me ratio) unchanged before and after supplying to the firing device 1 (FIGS. 2-3) of the present invention.
[0065] Since the required value of the Li / Me ratio varies depending on the configuration of the secondary battery, the value of the Li / Me ratio can be appropriately set within the above range according to the requirement. The value of the Li / Me ratio may be, for example, 0.95 or more and less than 1.03, 1.0 or more and less than 1.03, or more than 1.0 and less than 1.03.
[0066] In addition, since the Li / Me ratio is almost unchanged before and after the firing step (step S30), the Li / Me ratio in the lithium mixture is almost maintained in the lithium nickel composite oxide. Therefore, the mixing ratio of the nickel composite oxide and the lithium compound can be appropriately adjusted so that it is the same as the Li / Me ratio in the lithium nickel composite oxide to be obtained.
[0067] A general mixer can be used to mix the nickel composite oxide and the lithium compound, such as a shaker mixer, a Loedige mixer, a Julia mixer, or a V blender. This mixing should be sufficient so long as the nickel composite oxide is not destroyed. If the mixing is not sufficient, the Li / Me ratio may vary between individual particles, resulting in problems such as insufficient battery characteristics.
[0068] When the Li / Me ratio is appropriately mixed as described above, the mixture is filled into a flexible container (reference numeral 80 in FIG. 3) or the like. Then, the mixed powder raw material is supplied from the flexible container 80 to the hopper 50 in the supply unit 10 of the firing device 1 shown in FIG. 3 before the firing process. Furthermore, the mixed powder raw material is filled from the hopper 50 into the setter S of the firing device 1 as the material to be fired, and the process from firing to discharge is carried out.
[0069] (Baking: Step S30) In the firing step (S30) shown in the process diagram of Fig. 5, the material to be fired is fired in an oxygen atmosphere at 650°C to 1100°C. By firing the material to be fired, the nickel-cobalt composite oxide reacts with the lithium compound to produce a lithium-nickel composite oxide. By firing the material to be fired at the above temperature, a lithium-nickel composite oxide (positive electrode active material) having high crystallinity equal to or higher than that of the conventional material can be obtained in a much shorter time than the conventional firing time.
[0070] The firing conditions are not particularly limited as long as the nickel composite oxide and the lithium compound in the fired material react to form a lithium nickel composite oxide. For example, it is preferable to gradually increase the temperature from room temperature and hold it at a temperature range of 650°C to 1100°C for 3 hours or less. If the firing temperature is less than 650°C, lithium diffusion may not be sufficient, unreacted lithium compound particles may remain, or the crystal structure of the lithium nickel composite oxide may not be fully aligned, so that a secondary battery using the obtained positive electrode active material may not have sufficient battery characteristics. On the other hand, if the firing temperature is more than 1100°C, intense sintering may occur between the lithium nickel composite oxide particles and abnormal grain growth may occur, resulting in a decrease in the specific surface area. In addition, the specific surface area of the positive electrode active material may decrease, causing the resistance of the positive electrode in the secondary battery to increase and the battery capacity to decrease.
[0071] The firing temperature can be adjusted as appropriate depending on the composition and shape of the material to be fired. For example, when the other element M of the nickel composite oxide is aluminum (Al) and the lithium compound is lithium hydroxide, the firing temperature may be in the range of 700°C to 800°C, and is preferably in the range of 730°C to 770°C, and this temperature can be maintained for about 2 to 5 hours. When the other element is manganese and the lithium compound is lithium carbonate, the firing temperature is in the range of about 850 to 1050°C, and this temperature can be maintained for about 6 to 15 hours.
[0072] The time for which the material to be fired is held at the firing temperature (hereinafter also referred to as "holding time") is not particularly limited as long as a lithium nickel composite oxide having high crystallinity is formed, but may be, for example, 5 hours or less, and preferably 3 hours or less. The shorter the firing time, the higher the productivity. The lower limit of the firing time may be, for example, 2.5 hours or more.
[0073] The atmosphere during firing is preferably an oxidizing atmosphere having an oxygen concentration equal to or higher than that of the air atmosphere, more preferably an atmosphere having an oxygen concentration of 80% by volume or more, and may be an oxygen concentration of 100% by volume. That is, the firing atmosphere is preferably performed in an oxygen stream. If the oxygen concentration is less than 80% by volume, it may be impossible to supply the amount of oxygen necessary for the reaction between the nickel composite oxide and the lithium compound, and the lithium nickel composite oxide may not be sufficiently formed.
[0074] The firing furnace is not particularly limited, and may be any furnace capable of heating in an oxygen stream, such as a vertical furnace, a rotary hearth furnace, a roller hearth kiln, etc. Among these, it is preferable to use a roller hearth kiln from the viewpoint of capital investment and running costs.
[0075] (Lithium nickel composite oxide treatment steps S40 to S60) FIG. 7 is a diagram showing an example of a process for treating the lithium nickel composite oxide obtained after calcination. As shown in the figure, the method for producing a positive electrode active material according to this embodiment includes crushing the lithium nickel composite oxide (calcined product) obtained after the calcination process (step S30) to obtain a crushed product (powders of lithium nickel composite oxide) (crushing process: step S40), washing the crushed product with water and filtering (water washing process: step S50), and drying the washed lithium nickel composite oxide (drying process: step S60). The method for producing a positive electrode active material according to this embodiment may not include the above-mentioned crushing (step S40), water washing (step S50), and drying process (step S60), or may include at least one of these three processes. Each process will be described below.
[0076] (Crushing process: step S40) The lithium nickel composite oxide (calcined product) obtained after the calcination (step S30) may be further crushed (step S40). By crushing, secondary particles of the lithium nickel composite oxide that have undergone aggregation or slight sintering can be separated from each other, and the average particle size and particle size distribution of the obtained positive electrode active material can be adjusted to a suitable range. In addition, since the obtained calcined product generates bonds between particles during the calcination reaction, it is preferable to crush it (step S40). Note that, crushing refers to an operation of applying mechanical energy to agglomerates consisting of a plurality of secondary particles generated by sintering necking between secondary particles during calcination, separating the agglomerates with almost no destruction of the secondary particles themselves, and loosening the agglomerates.
[0077] As a crushing method, known means can be used, for example, a pin mill, a hammer mill, a crusher with a classification function, etc. In this case, it is preferable to adjust the crushing force within an appropriate range so as not to destroy the secondary particles.
[0078] (Water washing process: step S50) Next, the crushed material obtained may be washed with water (step S50). By washing the lithium nickel composite oxide (crushed material) with water, excess lithium and impurities on the surface of the lithium nickel composite oxide particles are removed, and a positive electrode active material for lithium ion secondary batteries having a higher capacity and higher thermal stability can be obtained. Here, the washing method is not particularly limited, and a known technique can be used.
[0079] As a method of washing with water, for example, the lithium nickel composite oxide (crushed material) is put into water to make a slurry, and the slurry is preferably stirred so that excess lithium on the particle surfaces of the lithium nickel composite oxide is sufficiently removed. After stirring, the slurry is separated into solid and liquid, and dried (step S60) as described later to obtain the lithium nickel composite oxide.
[0080] As for the slurry concentration, it is preferable to add 0.5 to 2 parts by mass of the lithium nickel composite oxide (crushed material) per 1 part by mass of water. If the amount of the crushed material added per 1 part by mass of water is more than 2 parts by mass, the viscosity becomes very high and stirring becomes difficult, and the alkali in the liquid is high, so that the dissolution rate of the attached matter slows down due to the equilibrium relationship, and even if peeling occurs, separation from the powder becomes difficult. On the other hand, if the amount of the crushed material added per 1 part by mass of water is less than 0.5 parts by mass, the slurry is too dilute, so that the amount of lithium elution is large, and lithium is also released from the crystal lattice of the lithium nickel composite oxide (crushed material), making the crystals more likely to collapse, and the high pH aqueous solution (slurry) absorbs carbon dioxide gas in the air, and lithium carbonate may be reprecipitated on the surface of the lithium nickel composite oxide.
[0081] The washing liquid used in the water washing step (step S50) is not particularly limited, and may be, for example, water. When water is used, for example, water with a measured electrical conductivity of less than 10 μS / cm is preferred, and water with a measured electrical conductivity of 1 μS / cm or less is more preferred. When water with a measured electrical conductivity of less than 10 μS / cm is used, the deterioration of battery performance due to adhesion of impurities to the positive electrode active material can be further suppressed.
[0082] When the slurry is subjected to solid-liquid separation, it is preferable that the amount of water remaining on the surface of the lithium nickel composite oxide particles is small. If the amount of water remaining is large, lithium dissolved in the liquid (slurry) may be reprecipitated, and the amount of lithium present on the surface of the lithium nickel composite oxide after drying (step S60) may increase. For solid-liquid separation, a commonly used centrifuge, filter press, etc. may be used.
[0083] (Drying process: Step S60) After washing with water (step S50), drying may be performed to obtain a lithium nickel composite oxide (cathode active material) (step S60). The drying conditions are not particularly limited as long as at least a part of the moisture in the lithium nickel composite oxide is removed. The drying step (step S60) is preferably performed at a predetermined temperature using a dryer that can control, for example, the lithium nickel composite oxide (powder) after filtration (solid-liquid separation) in a gas atmosphere containing no compound components containing carbon and sulfur or in a vacuum atmosphere.
[0084] The drying temperature is preferably 80°C or higher and 550°C or lower, more preferably 120°C or higher and 350°C or lower. When the drying temperature is 80°C or higher, the cathode active material after washing with water (step S50) can be quickly dried, and it is possible to suppress the occurrence of a lithium concentration gradient between the particle surface and the particle interior. On the other hand, when the drying temperature exceeds 550°C, it is expected that some lithium has desorbed and the material is in a state close to the charged state. Therefore, since the crystal structure near the surface of the lithium nickel composite oxide collapses starting from the site where lithium has desorbed, there is a risk of deterioration of the battery characteristics in the secondary battery. Also, from the viewpoints of productivity and thermal energy cost, the drying temperature is more preferably 120°C or higher and 350°C or lower.
[0085] (4) Cathode active material By the above-described method for manufacturing a cathode active material, a lithium nickel composite oxide (cathode active material) having excellent crystallinity can be obtained with high productivity by firing for a very short time. Hereinafter, the characteristics of the lithium nickel composite oxide (cathode active material) obtained by this manufacturing method will be described.
[0086] (Composition) The lithium nickel composite oxide contains lithium (Li), nickel (Ni), cobalt (Co), and an optional element (M), and the molar ratio of each metal element is Li:Ni:Co:M = s:(1 - x - y):x:y (where 0.93 < s < 1.03, 0.00 ≦ x ≦ 0.35, 0.03 ≦ y ≦ 0.35, and M is one or more transition metals, alkaline earth metals, base metals, or metalloids).
[0087] (Lithium seat occupancy rate) The lithium nickel composite oxide has a lithium site occupancy of 95% or more, preferably 96% or more, and more preferably 97% or more, of the 3a site, which is a lithium-dominated layer, obtained by, for example, Rietveld analysis of an X-ray diffraction pattern. When the lithium site occupancy is within the above range, the sintering reaction between the precursor and the lithium compound is sufficiently carried out in the firing step (step S30), and the lithium nickel composite oxide has high crystallinity. When a lithium nickel composite oxide with high crystallinity is used as a positive electrode active material for a secondary battery, it exhibits excellent battery characteristics (high battery capacity, etc.).
[0088] (amount of dissolved lithium) The lithium nickel composite oxide has an amount of lithium eluted into water when the lithium nickel composite oxide is dispersed in water (amount of eluted lithium) of, for example, 0.11% by mass or less, preferably 0.10% by mass or less, and more preferably 0.05% by mass or less, based on the total amount of the lithium nickel composite oxide. The amount of eluted lithium can be measured by neutralization titration. When a water washing step (step S50) is performed, the amount of eluted lithium is a value measured using the lithium nickel composite oxide obtained after water washing (step S50) and drying (step S60).
[0089] The eluted lithium is considered to originate from unreacted lithium compounds present on the particle surface of the lithium nickel composite oxide (positive electrode active material) and excess lithium present in the crystals. That is, the amount of eluted lithium can be used as an index showing the remaining amount of unreacted lithium compounds derived from the raw material, and it can be said that the smaller the amount of eluted lithium, the smaller the remaining amount of unreacted lithium compounds, and the more the sintering reaction between the precursor and the lithium compounds has progressed. In addition, the smaller the amount of eluted lithium, the more the gelation of the positive electrode composite paste can be suppressed.
[0090] The amount of eluted lithium is a value calculated by dispersing 15 g of lithium nickel composite oxide in 75 ml of pure water, leaving it to stand for 10 minutes, diluting 10 ml of the supernatant with 50 ml of pure water, and measuring the amount of lithium eluted in the water (amount of eluted lithium) by neutralization titration by adding 1 mol / L hydrochloric acid.
[0091] (Initial charge / discharge efficiency) In a 2032-type coin-type battery CBA (see FIG. 8) for evaluation produced using a lithium nickel composite oxide as a positive electrode active material, the initial charge / discharge efficiency (initial discharge capacity / initial charge capacity) is, for example, 85% or more, preferably 89% or more, and more preferably 89.5% or more. When the initial charge-discharge efficiency is within the above range, the sintering reaction between the precursor and the lithium compound is sufficiently carried out in the firing step (step S30), and the lithium nickel composite oxide has high crystallinity. The initial discharge capacity efficiency was measured by leaving the coin cell CBA used in the examples for about 24 hours after production, and after the open circuit voltage OCV (Open Circuit Voltage) was stabilized, and then applying a current density of 0.1 mA / cm to the positive electrode. 2 The capacity was measured when the battery was charged to a cut-off voltage of 4.3 V, then allowed to rest for one hour, and then discharged to a cut-off voltage of 3.0 V.
[0092] (5) Lithium-ion secondary battery The lithium ion secondary battery described below is composed of a positive electrode, a negative electrode, and a non-aqueous electrolyte. The positive electrode is obtained by using the positive electrode active material obtained by the above-mentioned manufacturing method. The secondary battery other than the above may, for example, include a positive electrode, a negative electrode, a separator, and a non-aqueous electrolyte, or may include a positive electrode, a negative electrode, and a solid electrolyte. The secondary battery may also be composed of the same components as known lithium ion secondary batteries. Hereinafter, each of the constituent materials of a secondary battery using a non-aqueous electrolyte solution and a method for producing the same will be described.
[0093] (positive electrode) The positive electrode is formed using the positive electrode active material described above. First, the positive electrode active material, conductive material, and binder are mixed, and activated carbon and a solvent for viscosity adjustment, etc. are added as necessary, and the mixture is kneaded to prepare a positive electrode composite paste. Note that the constituent materials of the positive electrode composite paste are not particularly limited, and materials equivalent to known positive electrode composite pastes may be used. The mixing ratio of each material in the positive electrode composite paste is not particularly limited and is adjusted appropriately according to the required performance of the secondary battery. The mixing ratio of the materials can be in the same range as that of the positive electrode composite paste of a known secondary battery, and for example, when the total mass of the solid content of the positive electrode composite excluding the solvent is 100 parts by mass, the content of the positive electrode active material may be 60 parts by mass or more and 95 parts by mass or less, the content of the conductive material may be 1 part by mass or more and 20 parts by mass or less, and the content of the binder may be 1 part by mass or more and 20 parts by mass or less. As the conductive agent, for example, graphite (natural graphite, artificial graphite, expanded graphite, etc.), acetylene black, Ketjen black, and other carbon black-based materials can be used. The binder serves to bind the active material particles together, and examples of the binder that can be used include polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), fluororubber, ethylene propylene diene rubber, styrene butadiene, cellulose-based resin, and polyacrylic acid. If necessary, a solvent for dispersing the positive electrode active material, conductive material, and activated carbon and dissolving the binder (binding agent) may be added to the positive electrode mixture paste. Specifically, an organic solvent such as N-methyl-2-pyrrolidone (NMP) may be used as the solvent. Activated carbon may be added to the positive electrode mixture in order to increase the electric double layer capacity. Next, the obtained positive electrode composite paste is applied to the surface of a current collector made of, for example, aluminum foil, dried, and the solvent is removed to prepare a sheet-shaped positive electrode. If necessary, pressure may be applied by a roll press or the like to increase the electrode density. The sheet-shaped positive electrode can be cut to an appropriate size according to the desired battery and used to prepare the battery.
[0094] (Negative electrode) The negative electrode may be made of metallic lithium, a lithium alloy, etc. The negative electrode may be made by mixing a binder with a negative electrode active material capable of absorbing and desorbing lithium ions, adding an appropriate solvent to the negative electrode mixture to make a paste, applying the paste to the surface of a metal foil current collector such as copper, drying the paste, and compressing the paste to increase the electrode density as necessary. As the negative electrode active material, for example, natural graphite, artificial graphite, a calcined organic compound such as phenolic resin, or a powder of a carbon material such as coke can be used. As the negative electrode binder, a fluorine-containing resin such as PVDF can be used, as in the positive electrode. As the solvent for dispersing these active materials and binders, an organic solvent such as N-methyl-2-pyrrolidone can be used.
[0095] (Separator) A separator is sandwiched between the positive electrode and the negative electrode. The separator separates the positive electrode and the negative electrode and retains the electrolyte. A thin membrane made of polyethylene, polypropylene, or the like and having many minute pores can be used as the separator.
[0096] (Non-aqueous electrolyte) As the non-aqueous electrolyte, for example, a non-aqueous electrolytic solution can be used. As the non-aqueous electrolyte, for example, a solution in which a lithium salt as a supporting salt is dissolved in an organic solvent can be used. Alternatively, as the non-aqueous electrolyte, a solution in which a lithium salt is dissolved in an ionic liquid can be used. Note that the ionic liquid refers to a salt that is composed of cations and anions other than lithium ions and is liquid even at room temperature. The organic solvent may be one selected from cyclic carbonates such as ethylene carbonate, propylene carbonate, butylene carbonate, and trifluoropropylene carbonate; chain carbonates such as diethyl carbonate, dimethyl carbonate, ethyl methyl carbonate, and dipropyl carbonate; ether compounds such as tetrahydrofuran, 2-methyltetrahydrofuran, and dimethoxyethane; sulfur compounds such as ethyl methyl sulfone and butane sultone; and phosphorus compounds such as triethyl phosphate and trioctyl phosphate. Two or more of these organic solvents may be used in combination. The supporting salt may be LiPF6, LiBF4, LiClO4, LiAsF6, LiN(CF3SO2)2, or a composite salt thereof. Furthermore, the non-aqueous electrolyte may contain a radical scavenger, a surfactant, a flame retardant, and the like. The non-aqueous electrolyte may be a solid electrolyte. The solid electrolyte has a property of being able to withstand high voltage. Examples of the solid electrolyte include inorganic solid electrolytes and organic solid electrolytes. Examples of the inorganic solid electrolyte include oxide-based solid electrolytes and sulfide-based solid electrolytes. The oxide-based solid electrolyte is not particularly limited, and for example, an oxide-based solid electrolyte containing oxygen (O) and having lithium ion conductivity and electronic insulation can be suitably used. Examples of the oxide-based solid electrolyte include lithium phosphate (Li3PO4), Li3PO4N X , LiBON X , LiNbO3, LiTaO3, Li2SiO3, Li4SiO4-Li3PO4, Li4SiO4-Li3VO4, Li2O-B2O3-P2O5, Li2O-SiO2, Li2O-B2O3-ZnO, Li 1+X Al X Ti 2-X (PO4)3(0≦X≦1), Li 1+X Al X Ge 2-X (PO4)3(0≦X≦1), LiTi2(PO4)3, Li 3X La 2 / 3-X TiO3(0≦X≦2 / 3), Li5La3Ta2O 12, Li7La3Zr2O 12 , Li6BaLa2Ta2O 12 , Li 3.6 S 0.6 P 0.4 One or more types selected from O4, etc. can be used. The sulfide-based solid electrolyte is not particularly limited, and for example, one containing sulfur (S) and having lithium ion conductivity and electronic insulation can be suitably used. For example, the sulfide-based solid electrolyte can be one or more selected from Li2S-P2S5, Li2S-SiS2, LiI-Li2S-SiS2, LiI-Li2S-P2S5, LiI-Li2S-B2S3, Li3PO4-Li2S-Si2S, Li3PO4-Li2S-SiS2, LiPO4-Li2S-SiS, LiI-Li2S-P2O5, LiI-Li3PO4-P2S5, etc. The organic solid electrolyte is not particularly limited as long as it is a polymer compound exhibiting ion conductivity, and examples of the organic solid electrolyte that can be used include polyethylene oxide, polypropylene oxide, copolymers thereof, etc. The organic solid electrolyte may also contain a supporting salt (lithium salt).
[0097] (Battery shape and configuration) The shape of the lithium ion secondary battery composed of the above positive electrode, negative electrode, and non-aqueous electrolyte can be various, such as a cylindrical type, a laminated type, etc. Regardless of the shape, the positive electrode and the negative electrode are laminated via a separator to form an electrode body, the obtained electrode body is impregnated with a non-aqueous electrolyte solution, the positive electrode current collector and the positive electrode terminal connected to the outside, and the negative electrode current collector and the negative electrode terminal connected to the outside are connected using a current collector lead or the like, and the battery is sealed in a battery case to complete the lithium ion secondary battery. In addition, when a solid electrolyte is used, the solid electrolyte may also serve as a separator. EXAMPLES
[0098] (6) Example of lithium-ion secondary battery Hereinafter, an embodiment of a lithium ion secondary battery using a positive electrode active material obtained using the illustrated hopper 50 and sintering device 1 will be described. The performance (stability of paste, initial discharge capacity, positive electrode resistance, discharge capacity retention rate) of the positive electrode active material of (4) and the lithium ion secondary battery using this positive electrode active material was measured. In this example, each sample of special grade reagents manufactured by Wako Pure Chemical Industries, Ltd. was used for the production of the composite hydroxide, the positive electrode active material, and the secondary battery.
[0099] (Production and evaluation of secondary batteries for evaluation) A 2032-type coin-type battery CBA (see FIG. 8) was produced by the following method, and the battery characteristics of the positive electrode active material were evaluated.
[0100] (Making coin-cell batteries) 52.5 mg of the positive electrode active material, 15 mg of acetylene black, and 7.5 mg of polytetrafluoroethylene resin (PTFE) were mixed and pressed at a pressure of 100 MPa to produce a positive electrode PE (electrode for evaluation) with a diameter of 11 mm and a thickness of 100 μm. The produced positive electrode PE was dried in a vacuum dryer at 120°C for 12 hours. The dried positive electrode D1, negative electrode D3, separator D2, and electrolyte were used to produce a coin-type battery CBA shown in FIG. 8 in a glove box in an Ar atmosphere with a dew point controlled at -80°C.
[0101] For the negative electrode D3, a negative electrode sheet was used in which graphite powder with an average particle size of about 20 μm and polyvinylidene fluoride were applied to copper foil, punched into a disk shape with a diameter of 14 mm, and for the electrolyte, an equal mixture of ethylene carbonate (EC) and diethyl carbonate (DEC) with 1M LiPF6 as the supporting electrolyte (manufactured by Toyama Pharmaceutical Co., Ltd.) was used. For the separator D2, a polyethylene porous film with a thickness of 25 μm was used. In addition, the coin-type battery CBA had a gasket D4 and a wave washer, and was assembled into a coin-type battery with a positive electrode can D5 and a negative electrode can D6.
[0102] (Initial discharge capacity) The initial discharge capacity was measured by leaving the coin cell CBA for about 24 hours after production, and after the open circuit voltage OCV (Open Circuit Voltage) had stabilized, applying a current density of 0.1 mA / cm to the positive electrode. 2The battery was charged to a cut-off voltage of 4.3 V, and after one hour of rest, the capacity at which the battery was discharged to a cut-off voltage of 3.0 V was defined as the initial discharge capacity.
[0103] (Lithium dissolution titration) 15 g of the obtained lithium nickel composite oxide (positive electrode active material) was dispersed in 75 ml of pure water and then allowed to stand for 10 minutes. 10 ml of the supernatant was diluted with 50 ml of pure water, and the amount of lithium dissolved in the water (amount of dissolved lithium) was measured by neutralization titration by adding 1 mol / L hydrochloric acid.
[0104] (Lithium content) The lithium content was determined by analyzing each metal element and calculating the ratio of lithium to other metals (Li / Me ratio). The analysis of each metal element was performed using ICP, and the analytical samples were prepared by dissolving the fired products of each Example and Comparative Example.
[0105] Example 1 A nickel composite oxide obtained by oxidizing and roasting a nickel composite hydroxide with a composition ratio of Ni:Co:Al = 88:9:3 in a rotary kiln was mixed with lithium hydroxide with a moisture content of 1.5% or less and a total carbon content of 1.0% or less so that the Li / Me ratio was 1.03 to prepare a lithium mixture (this is the material to be calcined). The maximum angle of repose of the lithium mixture prepared was 65°. This lithium mixture was sintered using a sintering device 1 (FIGS. 1 and 2) to obtain a sintered product. In detail, 48 kg of the lithium mixture was charged into a hopper 50 (FIG. 1) made of SUS304 and with a cone opening angle of 40°. From this hopper 50, 4 kg was charged into a box-shaped setter S using a charging machine, and sintered at 760°C using a sintering furnace 2 (roller hearth kiln), obtaining 12 sintered products. A small solidified layer with a thickness of about 20 mm was formed on the inner surface of the hopper 50, but the solidified layer was destroyed by vibration using a bridge breaker installed in the hopper 50, and the entire amount of the lithium mixture was discharged. Table 1 shows an evaluation of the occurrence of a solidified layer and the variation in the mixing ratio. The twelve pieces of the fired material were each crushed to less than 1 mm, and the lithium content of each was analyzed. The twelve pieces of the positive electrode active material were mixed and homogenized to create a coin-type battery, and the initial discharge capacity was measured. The Li / Me ratio and initial discharge capacity of the fired material are also shown in Table 2.
[0106] Example 2 The same procedure was followed as in Example 1, except that the opening angle of the cone part of the hopper 50 was set to 30°. No solidified layer was observed inside the hopper 50, and the entire amount of the lithium mixture could be discharged. The evaluation of the presence or absence of a solidified layer and the variation in the mixture ratio are shown in Table 1. The Li / Me ratio and initial discharge capacity of the fired product are shown in Table 2.
[0107] Example 3 The composition ratio of the nickel composite oxide was Ni:Co:Al=91:4:5, the Li / Me ratio was 1.02, and the sintering temperature was 745°C, but the same procedure was followed as in Example 1. The maximum angle of repose of the lithium mixture produced was 63°. A small solidified layer with a thickness of about 15 mm was formed on the inner wall 52a of the cone portion 52, but the solidified layer was destroyed by vibration from a bridge breaker installed in the hopper 50, and the entire amount of the lithium mixture was discharged. Table 1 shows the evaluation of the occurrence of the solidified layer and the variation in the mixture ratio. Table 2 shows the Li / Me ratio and initial discharge capacity of the sintered product.
[0108] Example 4 The same procedure was followed as in Example 3, except that the opening angle of the cone part of the hopper 50 was set to 30°. No solidified layer was observed inside the hopper 50, and the entire amount of the lithium mixture could be discharged. The evaluation of the presence or absence of a solidified layer and the variation in the mixture ratio are shown in Table 1. The Li / Me ratio and initial discharge capacity of the fired product are shown in Table 2.
[0109] Comparative Example 1 The same procedure was followed as in Example 1, except that the opening angle of the cone part of the hopper 50 was set to 50°. A large solidified layer with a thickness of about 150 mm was formed inside the hopper 50. When the solidified layer was broken by a bridge breaker, the entire amount of the lithium mixture could be discharged. The evaluation of the occurrence of the solidified layer and the variation in the mixture ratio are shown in Table 1. The Li / Me ratio and initial discharge capacity of the fired product are shown in Table 2.
[0110] Comparative Example 2 The same procedure was followed as in Example 3, except that the opening angle of the cone part of the hopper 50 was set to 50°. A large solidified layer with a thickness of about 150 mm was formed on the inner wall 52a of the cone part 52. The solidified layer was broken by a bridge breaker, and the entire amount of the lithium mixture could be discharged. The evaluation of the occurrence of the solidified layer and the variation in the mixture ratio are shown in Table 1. The Li / Me ratio and initial discharge capacity of the fired product are shown in Table 2.
[0111] [Table 1]
[0112] [Table 2]
[0113] (Evaluation Results) (1) Variation in the Li / Me ratio of fired products In Examples 1 and 3, since the hopper of the first invention was used, some solidified layer was formed on the inner wall 52a of the cone portion 52, but the obtained lithium nickel composite oxide had a small variation in the Li / Me ratio. Therefore, the initial discharge capacity was stable, and the initial discharge capacity of the homogenized mixture was also high, resulting in a good positive electrode active material. In addition, in Examples 2 and 4, no solidified layer was formed on the inner wall 52a of the cone portion 52 and the entire lithium mixture was discharged in a laminar flow, so that the variation in the Li / Me ratio was very small and the variation in the initial discharge capacity was also very small. Furthermore, the initial discharge capacity of the mixture was not reduced at all, even though it was homogenized, and an extremely good positive electrode active material was obtained. On the other hand, in Comparative Examples 1 and 2, a large solidified layer was formed on the inner wall 52a of the cone portion 52, and the variation in the Li / Me ratio became very large.
[0114] (2)Initial discharge capacity A comparison is made between an example and a comparative example having the same composition ratio. Comparing Examples 1 and 2, in which Ni:Co:Al is 88:9:3, with Comparative Example 1, the standard deviations of the Li / Me ratios in Examples 1 and 2 are 0.001 and 0.003, respectively, which are smaller in the variation of the mixture ratio than the 0.006 in Comparative Example 1. Reflecting this smaller variation, the initial discharge capacity in Examples 1 and 2 is about 210 mAh / g, which is higher than the approximately 206 mAh / g in Comparative Example 1. Comparing Examples 3 and 4, in which Ni:Co:Al is 91:4:5, with Comparative Example 2, the standard deviations of the Li / Me ratios in Examples 3 and 4 are 0.001 and 0.002, respectively, which are smaller than the 0.005 in Comparative Example 2. Reflecting this small variation, the initial discharge capacity in Examples 3 and 4 is about 213 mAh / g, which is higher than the approximately 209 mAh / g in Comparative Example 2. [Industrial Applicability]
[0115] The hopper of the present invention can be used for any mixed powder raw material as long as it supplies a mixed powder raw material containing a plurality of powders. Therefore, the hopper of the present invention can be used not only for raw materials for positive electrode active materials for secondary batteries, but also for raw materials for positive electrode active materials for lithium ion secondary batteries. The firing apparatus of the present invention can be used for firing any object to be fired. Therefore, the firing apparatus of the present invention can be used not only for raw materials for positive electrode active materials for secondary batteries, but also for raw materials for positive electrode active materials for lithium ion secondary batteries. [Explanation of symbols]
[0116] 1. Baking equipment 2. Firing furnace 5. Conveyor 10 Supply section 20 Discharge section 21 Crushing Mechanism 50 Hopper 51 Hopper section 52 Cone section S Setter
Claims
1. A hopper for supplying a mixed powder raw material containing a nickel composite oxide and a lithium compound having different physical properties, A cylindrical hopper portion, A cone-shaped portion connected to a lower end of the hopper portion; a discharge portion connected to a lower end of the cone portion, The opening angle a of the cone portion is 40° or less. A hopper characterized by:
2. The opening angle a of the cone portion is 30° or less.
2. The hopper of claim 1.
3. The maximum angle of repose of the mixed powder raw material is 63° or more and 65° or less.
2. The hopper of claim 1.
4. A plurality of setters in which objects to be fired are filled; A supply unit that supplies an object to be sintered to each setter; a firing furnace for firing the objects to be fired supplied to each setter; a conveying section that conveys each setter from the supply section to the firing furnace and conveys each setter carrying the fired product fired in the firing furnace out of the firing furnace; a discharge section for discharging the fired material from each of the setters, The hopper according to claim 1 is used as a device for supplying the mixed powder raw material in the supply section.
2. A firing apparatus for firing a positive electrode active material for a secondary battery.
5. The discharge section is A crushing mechanism is provided for crushing the fired products discharged from each setter.
5. The apparatus for baking a positive electrode active material for a secondary battery according to claim 4.
6. The crushing mechanism is a roll crusher, Also equipped with a cooling mechanism for cooling the rolls that come into contact with the high-temperature baked product.
6. The apparatus for baking a positive electrode active material for a secondary battery according to claim 5.
7. At least one of the supply unit, the sintering furnace, the discharge unit, or the crushing mechanism, Equipped with a function to maintain the oxygen concentration around the work space at 80% or more 5. The apparatus for baking a positive electrode active material for a secondary battery according to claim 4.
8. The fired product is The lithium-nickel composite metal oxide contains lithium (Li), nickel (Ni), cobalt (Co), and another element (M), and the atomic ratio of the elements is expressed as Li:Ni:Co:M=s:(1-xy):x:y (where 0.93<s<1.03, 0.00≦x≦0.35, 0.03≦y≦0.35, and M is one or more transition metals, alkaline earth metals, base metals, or semimetals).
8. The apparatus for baking a positive electrode active material for a secondary battery according to claim 4, wherein the baking apparatus is a baking apparatus for a positive electrode active material for a secondary battery.
Citation Information
Patent Citations
Feed, storage and discharge method for granular and powdery particle
JP1989213182A
Powder feed hopper
JP1993046795U
Hopper and insertion cone for hopper
JP1994080189A
Hopper for powder and granule
JP2001039489A
Particulate material crusher
JP2003290673A